Elevating Literary Literacy: Navigating Reading Engagement in the Digital Age - Utami, Wulan Tri Puji; Mustadi, Ali; ., Supartinah; Rosyidah, Awal Nur Kholifatur; Arifa, Noorul; Arditama, Andreas Yoga (Journal of Ecohumanism, 2024)
The development of digital technology in the last decade has brought significant changes in the world of education, including how students access and understand literary literacy. In Indonesia, even though access to digital reading materials is getting easier, the reading interest of elementary school students is still relatively low. This study aims to measure the effectiveness of digital literary literacy in increasing the reading interest of Elementary School students, especially in Indonesian subjects. This study also explores the factors that support the successful implementation of digital literary literacy and how students' perception of literary texts in digital format is compared to traditional print formats. Through an approach that combines literary literacy with digital technology, this research offers a new approach to increasing students' interest in reading and understanding literary texts. Using digital reader applications, interactive platforms, and multimedia is considered a strategy that can make literary learning more interesting and relevant for the digital generation. However, the main challenge is ensuring the depth of student engagement and understanding when reading digital texts that tend to be shorter and shallow. The result shows that as many as 81% of the teachers totally agree that digital literacy makes it easier to access the various types of literary text, and more than 90% agreed that digital literary literacy helps and improves student helps students to be more involved in overall literary learning. While in practice, the results of this research can guide educators in designing more effective learning strategies. Thus, this research offers a new perspective to increase students' interest in reading through integrating literary literacy and digital technology.